Influence of learner knowledge and case complexity on handover accuracy and cognitive load: results from a simulation study. Issue 9 (September 2016) - Young, John Q; van Dijk, Savannah M; O'Sullivan, Patricia S; Custers, Eugene J; Irby, David M; ten Cate, Olle
Abstract : Context: The handover represents a high‐risk event in which errors are common and lead to patient harm. A better understanding of the cognitive mechanisms of handover errors is essential to improving handover education and practice. Objectives: This paper reports on an experiment conducted to study the effects of learner knowledge, case complexity (i.e. cases with or without a clear diagnosis) and their interaction on handover accuracy and cognitive load. Methods: Participants were 52 Dutch medical students in Years 2 and 6. The experiment employed a repeated‐measures design with two explanatory variables: case complexity (simple or complex) as the within‐subject variable, and learner knowledge (as indicated by illness script maturity) as the between‐subject covariate. The dependent variables were handover accuracy and cognitive load. Each participant performed a total of four simulated handovers involving two simple cases and two complex cases. Results: Higher illness script maturity predicted increased handover accuracy (p < 0.001) and lower cognitive load (p = 0.007). Case complexity did not independently affect either outcome. For handover accuracy, there was no interaction between case complexity and illness script maturity. For cognitive load, there was an interaction effect between illness script maturity and case complexity, indicating that more mature illness scripts reduced cognitive load less in complex cases than in simple cases. Conclusions: Students with more mature illness scripts performed more accurate handovers and experienced lower cognitive load. For cognitive load, these effects were more pronounced in simple than complex cases. If replicated, these findings suggest that handover curricula and protocols should provide support that varies according to the knowledge of the trainee. Abstract : Discuss ideas arising from the article atwww.mededuc.com discuss.